Stream Segregation in the Perception of Sinusoidally Amplitude-Modulated Tones - Dolležal, Lena-Vanessa (Public Library of Science, 2012)
Amplitude modulation can serve as a cue for segregating streams of sounds from different sources. Here we evaluate stream segregation in humans using ABA- sequences of sinusoidally amplitude modulated (SAM) tones. A and B represent SAM tones with the same carrier frequency (1000, 4000 Hz) and modulation depth (30, 100%). The modulation frequency of the A signals (f(modA)) was 30, 100 or 300 Hz, respectively. The modulation frequency of the B signals was up to four octaves higher (Δf(mod)). Three different ABA- tone patterns varying in tone duration and stimulus onset asynchrony were presented to evaluate the effect of forward suppression. Subjects indicated their 1- or 2-stream percept on a touch screen at the end of each ABA- sequence (presentation time 5 or 15 s). Tone pattern, f(modA), Δf(mod), carrier frequency, modulation depth and presentation time significantly affected the percentage of a 2-stream percept. The human psychophysical results are compared to responses of avian forebrain neurons evoked by different ABA- SAM tone conditions [1] that were broadly overlapping those of the present study. The neurons also showed significant effects of tone pattern and Δf(mod) that were comparable to effects observed in the present psychophysical study. Depending on the carrier frequency, modulation frequency, modulation depth and the width of the auditory filters, SAM tones may provide mainly temporal cues (sidebands fall within the range of the filter), spectral cues (sidebands fall outside the range of the filter) or possibly both. A computational model based on excitation pattern differences was used to predict the 50% threshold of 2-stream responses. In conditions for which the model predicts a considerably larger 50% threshold of 2-stream responses (i.e., larger Δf(mod) at threshold) than was observed, it is unlikely that spectral cues can provide an explanation of stream segregation by SAM.